The use of a trifurcation of the lateral antebrachial cutaneous nerve for digital nerve grafting - Chiu, Chee Kidd; Ng, E.S.; Ahmad, T.S. (Elsevier, 2009)
A 17-year-old male was stabbed. The digital nerves to his thumb and radial aspect of the index finger were divided completely and repaired with the FPL tendon and both tendons to the index finger. At 3-months postoperatively there was no recovery of sensibility and the repair was explored. The digital nerve repairs had ruptured at the branching of a large single cutaneous branch of the median nerve into three smaller digital nerves supplying the thumb and the radial aspect of the index finger. The neuroma was excised leaving a gap of 2 cm.